ACTION RESEARCH TO INVESTIGATE A LOCAL PROBLEM (Fiep Bulletin - online, 2020)
This article presents a proposal to investigate a local problem in the teaching-learning process contextualized to the contents addressed in the classroom. The research was developed through action research, which sought to investigate the contribution of a problematizing issue in the teaching of chemistry in a CTS approach. The methodological approach used was the qualitative one of interpretative nature, performed with 20 students of the third year of the night high school in a college of the state school system of the city of Ponta Grossa, PR which were appointed from A01 to A20. The procedures involved socioscientific issues related initially to the use of hydrocarbons, food and subsequently addressed to local issues related to the consumption and disposal of cooking oil. The data analysis allowed to observe that the interaction of students with the topics covered has advanced within a reflective process for building knowledge through problematization, recognizing chemistry as a discipline of social and human formation.